Evaluation of the Therapeutic Efficacy of Antiretroviral Drugs used in the Clinical Management of HIV/AIDS Infection - Anochie PI; Afocha E; Onyeneke EC; Onyeozirila AC; Okoihue A; Ogu AC (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
The protease inhibitors are potent antiretroviral drugs because the protease activity is absolutely essential for production of infectious viruses. The newest class of drugs is the fusion inhibitors that blocks virus entry into cells. Persistent virus production is facilitated further by sub-inhibitory drug levels in infected cells or by host immune failure. Therefore, pre-existing or newly produced drug resistant mutants can emerge that have a selective advantage under drug pressure. These escape mutants become dominant in the virus population and lead to viral rebound and therapy failure. This review provides knowledge for improvement of antiretroviral drug administration programmes.